2022
DOI: 10.3390/bios12020132
|View full text |Cite
|
Sign up to set email alerts
|

The Introduction of a New Diagnostic Tool in Forensic Pathology: LiDAR Sensor for 3D Autopsy Documentation

Abstract: Autopsy is a complex and unrepeatable procedure. It is essential to have the possibility of reviewing the autoptic findings, especially when it is done for medico-legal purposes. Traditional photography is not always adequate to record forensic practice since two-dimensional images could lead to distortion and misinterpretation. Three-dimensional (3D) reconstructions of autoptic findings could be a new way to document the autopsy. Besides, nowadays, smartphones and tablets equipped with a LiDAR sensor make it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…These individual laser dots bounce off surrounding objects and surfaces, ultimately returning to the sensor [20]. Developers may access these data to create a 3D model based on the depth map and photographic information [21]. Although only a few years old, several studies have examined the application of the iPhone LiDAR scanning technology to forensic investigations.…”
Section: Iphone Lidar Sensormentioning
confidence: 99%
See 2 more Smart Citations
“…These individual laser dots bounce off surrounding objects and surfaces, ultimately returning to the sensor [20]. Developers may access these data to create a 3D model based on the depth map and photographic information [21]. Although only a few years old, several studies have examined the application of the iPhone LiDAR scanning technology to forensic investigations.…”
Section: Iphone Lidar Sensormentioning
confidence: 99%
“…Although only a few years old, several studies have examined the application of the iPhone LiDAR scanning technology to forensic investigations. Human body measurements including autopsy documentation by forensic pathologists tested the iPhone LiDAR scanner with success [14,20,21]. Maiese et al [21] concluded several notable advantages including ease of operation, no specialized skills necessary, affordability, and improved jury comprehension during trials [22].…”
Section: Iphone Lidar Sensormentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Maiese et al [ 30 ] used an iPad Pro equipped with a LiDAR sensor to elaborate 3D models obtained during ten autopsies in order to evaluate the quality and trustworthiness of these models compared to conventional autopsy photographic records. According to Fineschi et al, two apps were used to acquire scans (TRNIO and 3D Scanner), and the 3D models acquired were then processed using the MeshLab software.…”
Section: Introductionmentioning
confidence: 99%
“…Accurate documentation requires extensive training, anatomical knowledge, and precise notations can vary from pathologist to pathologist [6]. Digital technologies offer clear opportunities to streamline and systematise procedures beyond what is possible with paper-based methods and might ultimately improve the accuracy and precision of documentation [7, 8, 9]. For example, rendering the results of an autopsy examination with a digital platform could allow a pathologist to interact with a three-dimensional model of the body, zoom in and out of important anatomical regions and use standardised annotation tools.…”
Section: Introductionmentioning
confidence: 99%